PERBANDINGAN ALGORITMA KEMIRIPAN TEKS UNTUK PERBAIKAN DAN SARAN PENULISAN FRASA DALAM BAHASA ALAMI - Sembilu, Nambi; Samopa, Febriliyan; Er, Mahendrawathi (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2018)
Natural Language Processing (NLP) is a branch of science Aritificial Intelligence (AI) that focuses on natural language processing. Natural language is the language generally used by humans to communicate with each other. One of the problems in the use of natural language that is write error the word nor the structure of the word in a sentence. It also results in natural language processing into a computer is not able to get maximum results. So, to solve that problem in this research applies the Algorithm Oliver, LCS Algorithm (Longest Common Subsequences) of the Levenshtein Distance Algorithm and for improvement of writing as well as advising the writing. The results of the application of the Algorithm is shown in the third a simple application with a natural language interface as stuffed. The third test of the Algorithm shows good performance with the average ROC curve above 0.80. Then by comparing the performance of the Algorithm, the third is obtained that the LCS Algorithm has better performance in overcoming problems repair write error and the giving of advice with the indicated value of the ROC curve 0948.